Do Diatoms beneath the Greenland Ice Sheet Indicate Interglacials Warmer than Present? - Harwood, David M. (ARCTIC, 1986)
Basal sediment debris from the Greenland ice sheet was examined with the hope of recovering microfossils that could be used to determine and date changes in ice sheet size through time. Basal debris and debris-laden ice from the lower 18 m of the Camp Century ice core, northwest Greenland, revealed the presence of common freshwater and rare marine diatoms. These diatoms may have lived in the vicinity of the Camp Century site in the Late Neogene prior to development of the Greenland ice sheet. More likely, they lived during a Pleistocene interglacial period, when the volume of ice in the Greenland ice sheet was smaller than it is today and the site was ice free. A warmer and/or longer interglacial period than the present Holocene "interglacial" is suggested to explain the large decrease in ice sheet volume.Key words: diatoms, interglacial, Pleistocene, Camp Century ice core, Greenland Mots clés: diatomées, interglaciaire, Pléistocène, carotte de glace du Camp Century, Groenland